Resposta hemodinâmica materno-fetal à atividade física isométrica nas hipertensões da gestação - Kavalco, Tatiana Frehner (2020)
Objective: to evaluate the maternal-fetal hemodynamic by flow doppler parameters in response pregnant women with chronic systemic arterial hypertension (HAS) and with preeclampsia (PE) submitted to controlled isometric activity, comparing them with healthy patients. Methods: a crosssectional experimental study was carried out, with 50 healthy pregnant women (control group), 26 with HAS and 24 with PE, with gestational ages between 26 and 36 weeks, submitted to isometric effort activity with handgrip dynamometer and had maternal hemodynamic parameters (systolic blood pressure (PAS), diastolic (PAD), maternal heart rate (FCM) and uterine arteries (AU´s) Doppler) and fetal (heart rate, umbilical artery (AUm), middle cerebral artery ( MCA) and venous duct Doppler) verified before, during and after isometry. Results: the data demonstrated that, in the comparison of the groups, there were higher values in the PAS, PAD and pulsatility (IP), resistance (IR) and systole/diastole ratios (S/D) of the right and left AU's in pregnant women with PE in the three periods evaluated, as well as higher numbers in the IP and IR of the ACM in the pre and postisometric work and S/D of the ACM and FCM higher in the postisometric effort in the PE than in the healthy ones. When comparing the control group with chronic hypertensive women, PAS remained higher in all periods, the right AU and ACM indices were higher in pre-isometry, the ACM IP and all AUm indices were higher during the isometry and FCM and the IP and S/D of AUm remained higher after the isometry in the group with HAS. In healthy ones, only FCM transisometry was higher than in hypertensive women. In the comparison between the collection times, statistical significance was obtained for the control group in the increase of PAS and FCM and in the decrease of the left AU indices from pre to transisometry; in the decrease of PAS and FCM and in the increase of the PI of the right AU and of all the indices of the left AU from the trans to the postisometry. For the PE group, an increase in SBP and a decrease in the S / D of the right AU from the pre to the transisometry and the general variation of the DBP and the increase in the left AU indices from the trans to the post-isometry were confirmed. . In pregnant women with SAH, the increase in DBP and the decrease in the PI and IR of the right AU from the pre to the transisometry were ratified, as well as the increase in the PI and IR of the right AU and of all the indices of the left AU of the trans for post-contraction. Conclusion: there are higher PA values of pregnant women with PE and HAS, but with most significant increase from rest to isometry in healthy and PE patients; and with a relevant decrease from isometry to resting in healthy women. The right AU has greater resistance in patients with PE; with significant decrease of this resistance from rest to isometry in pregnant women with PE and HAS and with their increased from effort to rest in healthy and with chronic HAS. The left AU had decreased resistance before healthy women isometry and its resistance increases significantly post-contraction in all patients. The fetal hemodynamic parameters did not show significant differences when comparing the before, during and post-isometry.